Method for low-cost selective laser melting printing of titanium alloy
By expanding the particle size range of TC4 titanium alloy powder to 15-100μm, combined with large layer thickness and optimized process parameters, the problem of the particle size range of TC4 titanium alloy powder in the prior art is solved, and efficient and low-cost titanium alloy forming is achieved, and the density and mechanical properties of the formed parts are significantly improved.
Patent Information
- Application Number
- CN202510486924.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-08-08
AI Technical Summary
In the prior art, the particle size range of TC4 titanium alloy powder is too narrow, resulting in waste of resources, low forming efficiency, limited forming quality, and mismatch between powder and process parameters.
The scanning strategy is optimized to ensure the high density and high performance of the forming parts with a particle size range of 15-100μm.
It significantly improves powder utilization, reduces production costs, improves forming efficiency and forming quality, and the density of forming parts reaches more than 99.9%, excellent mechanical properties, and meets high-performance engineering needs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy material preparation, and in particular to a method for low-cost selective laser melting and printing of titanium alloy. Background Art
[0002] Selective Laser Melting (SLM) is a typical metal additive manufacturing technology. It uses the heat of a laser beam to completely melt and solidify metal powder based on a 3D model, producing metal parts with excellent metallurgical bonding and high precision. This technology is particularly suitable for manufacturing precision components with thin walls, complex cavities, and internal flow channels, which are difficult to achieve with traditional machining methods. The resulting parts exhibit fine, dense microstructures, uniform composition, and excellent performance. Due to its excellent processing characteristics, SLM technology is widely used in aerospace, automotive, medical, and other fields.
[0003] TC4 titanium alloy is widely used in the aforementioned fields due to its excellent mechanical properties (such as high specific strength, fatigue resistance, and biocompatibility). It is particularly suitable for manufacturing parts with complex shapes and high strength requirements using SLM technology. However, the particle size of TC4 titanium alloy powder cannot be ignored in the SLM forming process. In the existing technology, the particle size distribution range of TC4 titanium alloy powder suitable for SLM technology is generally 15-53μm. Studies have shown that if the powder particle size is less than 15μm, the powder is prone to agglomeration, resulting in poor powder fluidity and difficulty in evenly spreading on the substrate; if the powder particle size is greater than 53μm, the bulk density of the powder will decrease, resulting in discontinuous melting, which in turn makes the formed part have a low density and a rough surface.
[0004] Currently, TC4 titanium alloy powder for SLM is mostly produced using the electrode induction melting atomization (EIGA) process, with the resulting powder particle size typically ranging from 0 to 150μm. Improving the utilization of the powder particle size range while ensuring print quality and reducing production costs remains a key challenge in current technology. In particular, effectively utilizing both larger (greater than 53μm) and smaller (less than 15μm) particle sizes to achieve higher printing efficiency and maximize material utilization remains a pressing technical challenge.
[0005] Chinese patent application publication number CN114131043A discloses a method for improving the utilization rate of TC4 titanium alloy powder. This technology overcomes the limitations of traditional powder particle size range to a certain extent by expanding the use range of powder particle size (such as 15-75μm, 10-75μm, 10-90μm, 10-120μm, etc.), thereby improving the powder utilization rate. The advantage of this method is that it can expand the use range of powder particle size, but the forming process in the method is still limited by traditional layer thickness technology, resulting in certain limitations in the utilization of large-particle powder.
[0006] The Chinese patent application with publication number CN116875835A proposes a method of mixing fine powder (0-20μm) with coarse powder (75-100μm) to improve the void filling properties of the powder and increase the utilization rate of large-particle powder. However, due to the limitation of layer thickness during the printing process, this technology cannot effectively utilize coarse powder above 70μm, resulting in the potential of large-particle powder not being fully utilized, which in turn affects printing efficiency and forming quality.
[0007] A paper published by the School of Engineering at RMIT University in Australia and Siemens, titled "Systematic investigation of performance and productivity in laser powder bed fusion of Ti6Al4V up to 300µm layer thickness," systematically investigated the process-performance relationship for powder layers between 60µm and 300µm. While the study demonstrated the potential for large-layer-thickness printing, the powder particle size employed remained within the traditional 20-50μm range, indicating that even at large layer thicknesses, powders in this traditional particle size range still face limitations during the forming process.
[0008] Chinese patent application publication number CN117428208A increases layer thickness to 80µm to 160µm by optimizing process parameters, aiming to improve deposition efficiency. However, the TC4 powder particle size employed in this technology remains in the traditional 20-50µm range, failing to achieve significant raw material cost reductions. From a molding quality perspective, the technical requirement for a relative density of only 99% is relatively low. Furthermore, the patent application only provides hardness test results and does not include tensile testing, making it of limited reference value for practical engineering applications.
[0009] While these existing methods have addressed the limited range of powder particle sizes to some extent, they still haven't fully overcome the limitations of traditional low-layer-thickness printing techniques. For powders with particle sizes above 70μm, utilization is low at smaller layer thicknesses, resulting in low printing efficiency and reducing the overall value of large-particle powders. Therefore, effectively combining large-particle powders with high-layer-thickness printing processes has become a bottleneck in current technological development. Summary of the Invention
[0010] The first technical problem to be solved by the present invention is to provide a low-cost method for selective laser melting printing of titanium alloy, so as to overcome the problems in the prior art such as the narrow powder particle size range leading to waste of resources, low forming efficiency, limited forming quality and mismatch between powder and process parameters.
[0011] To overcome the above-mentioned defects of the prior art, the present invention provides a low-cost method for selective laser melting and printing titanium alloy, comprising the following steps: S1 provides TC4 titanium alloy powder, the titanium alloy powder having a particle size range of 15-100μm; S2. The TC4 titanium alloy powder was placed in a vacuum oven and dried to obtain printing material; S3. Pour the printing material into the selective laser melting device and set the process parameters, including: The laser power is 100-500W, the laser scanning speed is 700-1600mm / s, the printing layer thickness is 100-180μm, the laser track spacing is 0.05-0.15mm, and the scanning strategy is chessboard or partition; S4. Set the powder spreading speed during printing to complete printing of the target sample. S5. After printing is completed, the target sample is subjected to an annealing heat treatment at a temperature of 750-850° C. for 1.5-2.5 hours.
[0012] Compared with the prior art, the method of the present invention, which is a low-cost selective laser melting printing method for titanium alloy, has the following advantages: the method of the present invention not only solves the problems of low powder utilization, low forming efficiency, unstable forming quality and the like in the prior art by optimizing the combination of powder particle size, layer thickness and process parameters, but also greatly improves the production efficiency of TC4 titanium alloy and reduces the cost, providing a more efficient and economical solution for the 3D printing application of titanium alloy, which can achieve high-density, high-performance TC4 titanium alloy forming, and meet the high-efficiency, low-cost manufacturing requirements, and has significant technical advantages and market application potential; specifically, by expanding the powder particle size range to 15-100μm, larger particle size powder can be effectively utilized, which not only reduces the resource waste caused by the traditional powder particle size range (15-53μm), but also effectively reduces the material cost; the use of a larger printing layer thickness significantly improves the printing speed compared to the traditional low layer thickness (20-60μm), and reduces the time required for each layer during the printing process. By optimizing the layer thickness and matching the powder particle size, the large-particle powder is better utilized during the printing process, avoiding the problem of low forming efficiency caused by too small a layer thickness. In addition, the method of the present invention forms a reasonable match with the printing layer thickness and powder particle size by optimizing process parameters such as laser power, laser scanning speed, and laser track spacing, ensuring that the density of the formed part is stable at above 99.9%, especially at a layer thickness of 100μm, it can stably reach a density of 99.95%. This not only improves the mechanical properties of the formed part, but also avoids the problems of low density and rough surface of the formed part in the prior art. By optimizing the combination of powder particle size and layer thickness, the method of the present invention can greatly improve production efficiency while ensuring forming quality, thereby significantly reducing production costs. Compared with the 15-53μm particle size powder commonly used in the prior art, the present invention can reduce raw material costs by at least 30%, and by improving the utilization rate of powder, it greatly reduces waste in the production process.
[0013] In a possible implementation, in step S1, the particle size of the titanium alloy powder is in the range of 20-90 μm.
[0014] Compared with the existing technology, the above technical solution can further improve printing efficiency while taking into account the forming quality and powder utilization rate: the powder particle size range is further limited to 20-90μm, which effectively avoids the problem of uneven powder spreading caused by agglomeration of powder with too small particle size, and at the same time avoids the problem of insufficient melting of powder with too large particle size due to insufficient laser energy.
[0015] In a possible embodiment, in step S3, the process parameters include: laser power of 200W to 400W, laser scanning speed of 800mm / s to 1500mm / s, printing layer thickness of 100μm to 180μm, laser track spacing of 0.08mm to 0.12mm, and scanning strategy of chessboard or partition.
[0016] Compared with existing technologies, the above-mentioned technical solution can significantly improve the efficiency and forming quality of the selective laser melting (SLM) printing process. By optimizing the process parameters of laser power, scanning speed and printing layer thickness, each layer is melted more evenly, and the powder can be more fully integrated into the bottom layer and solidified, thereby reducing the problems of thermal distortion and cracks that may occur during the forming process. Specifically, by setting the laser power range to 200W to 400W, sufficient heat can be provided to melt powders with larger particle sizes, while avoiding excessive melting caused by excessive power and insufficient melting caused by too low power. Controlling the laser scanning speed between 800mm / s and 1500mm / s can not only increase the printing speed, but also ensure the heat exchange time between the laser beam and the powder, so that the powder in each area can be fully melted. The printing layer thickness is set to 100μm to 180μm, which effectively supports the printing of large-particle powders, ensuring that the powder can be evenly spread under large layer thickness conditions and ensuring the forming quality. The laser track spacing is set between 0.08mm and 0.12mm, which can avoid heat accumulation caused by too dense paths, and avoid too wide paths that cause the molten pool to cool too quickly, ensuring good melting quality. Setting the scanning strategy to chessboard or partitioning helps to improve heat transfer and reduce thermal stress, especially when printing with large layer thickness, which can effectively avoid thermal distortion and improve the density of the material.
[0017] In a possible implementation, in step S3, the scanning strategy is a scanning method with an inter-layer rotation of 67°, and a chessboard or partition scanning strategy is adopted between each layer.
[0018] Compared with the existing technology, the above technical solution adopts a scanning method with a 67° rotation between layers, which can effectively avoid the thermal stress concentration problem that may be caused by the traditional 90° scanning strategy. Through the 67° rotation method, especially when printing each layer, the direction of the heat source and the molten pool can be reasonably adjusted, thereby reducing problems such as warping and cracks caused by heat accumulation. The checkerboard or partitioned scanning strategy can form a more uniform heat distribution in the printing of each layer, and can improve the fluidity of the molten pool, preventing uneven melting caused by premature cooling of powder in some areas.
[0019] In a possible implementation, in step S4, the powder spreading speed is 8-50 mm / s.
[0020] Compared with the existing technology, the above technical solution can ensure the uniform distribution and good stacking density of each layer of powder by optimizing the powder laying speed range (8-50mm / s), thereby improving the melting efficiency of the powder and the density of the final molded part, thereby improving the printing quality and overall forming efficiency.
[0021] In a possible embodiment, in step S5, the annealing treatment condition is to raise the temperature to the annealing heat treatment temperature within 110-130 minutes, and then anneal.
[0022] Compared with existing technologies, the above-mentioned technical solution can make the microstructure of titanium alloy more uniform by controlling the heating rate and the precise temperature range, avoiding localized unevenness caused by rapid heating, such as excessively high or low temperatures, thereby improving the overall performance of the finished product. This optimized annealing process enables titanium alloy materials to exhibit superior mechanical properties and higher plasticity, especially in high-temperature environments, showing better tensile strength and yield strength. It significantly improves the mechanical properties of titanium alloy prints, especially in terms of tensile strength, yield strength, and elongation, ensuring that the material can meet high-performance engineering requirements.
[0023] In a possible implementation manner, in step S5, the annealing heat treatment temperature is 800° C., and the annealing heat treatment time is 2 hours.
[0024] Compared with the existing technology, the above-mentioned technical solution uses an annealing temperature of 800°C to help eliminate the residual stress generated by the selective laser melting process, reduce the warping and deformation that may occur during the forming process, and thus improve the dimensional stability and overall quality of the final product. The annealing time is 2 hours, which can ensure that the material is fully heated and homogenized at an appropriate temperature, further improving the density and reducing voids and other defects.
[0025] The second technical problem to be solved by the present invention is to provide a titanium alloy to overcome the problems of low density and low powder utilization rate of conventional titanium alloys in the prior art.
[0026] In order to overcome the above defects of the prior art, the present invention provides a titanium alloy prepared by the above method, wherein the density of the titanium alloy is ≥99.9%.
[0027] Compared with the existing technology, the titanium alloy printed by low-cost selective laser melting in the present application has the following advantages: the titanium alloy of the present invention optimizes the process parameters, especially controls the layer thickness, powder spreading speed, annealing treatment and other steps during the printing process, so that the density of the final titanium alloy material stably reaches more than 99.9%. In the existing technology, many printing processes have the problems of low density and many porosity, resulting in poor mechanical properties. The present invention overcomes this defect by improving the powder particle size range and adopting appropriate annealing temperature and processing time, thereby ensuring the high density and structural uniformity of the titanium alloy; another advantage of the titanium alloy of the present invention is that it improves the powder utilization rate. In the prior art, the particle size range of powder is usually concentrated in 15-53μm. Powders of this particle size are prone to problems such as poor fluidity and agglomeration during the forming process, and the utilization rate of large-particle powder is low. In contrast, the present invention adopts a powder particle size range of 15-100μm, which not only ensures the fluidity and spreadability of the powder, but also can more effectively utilize large-particle powder, thereby greatly improving the use efficiency of the powder and reducing production costs; through the above-mentioned process optimization, the density of the titanium alloy material is significantly improved, and the utilization rate of the powder is greatly improved, and the final printed part has excellent performance in mechanical properties. DETAILED DESCRIPTION
[0028] First, those skilled in the art should understand that these embodiments are merely for explaining the technical principles of the embodiments of the present application and are not intended to limit the scope of protection of the embodiments of the present application. Those skilled in the art may adjust them as needed to suit specific application scenarios.
[0029] The present invention provides a method for low-cost selective laser melting and printing of titanium alloy, comprising the following steps: S1 provides TC4 titanium alloy powder, the titanium alloy powder having a particle size range of 15-100μm; S2. The TC4 titanium alloy powder was placed in a vacuum oven and dried to obtain printing material; S3. Pour the printing material into the selective laser melting device and set the process parameters, including: The laser power is 100-500W, the laser scanning speed is 700-1600mm / s, the printing layer thickness is 100-180μm, the laser track spacing is 0.05-0.15mm, and the scanning strategy is chessboard or partition; S4. Set the powder spreading speed during printing to complete printing of the target sample. S5. After printing is completed, the target sample is subjected to an annealing heat treatment at a temperature of 750-850° C. for 1.5-2.5 hours.
[0030] As a preferred solution, in step S1, the particle size of the titanium alloy powder is in the range of 20-90 μm.
[0031] As a preferred solution, in step S3, the process parameters include: laser power of 200W to 400W, laser scanning speed of 800mm / s to 1500mm / s, printing layer thickness of 100μm to 180μm, laser track spacing of 0.08mm to 0.12mm, and scanning strategy of chessboard or partition.
[0032] As a preferred solution, in step S3, the scanning strategy is a scanning method with an inter-layer rotation of 67°, and a chessboard or partition scanning strategy is adopted between each layer.
[0033] As a preferred solution, in step S4, the powder spreading speed is 8-50 mm / s.
[0034] As a preferred solution, in step S5, the annealing treatment condition is to raise the temperature to the annealing heat treatment temperature within 110-130 minutes, and then anneal.
[0035] As a preferred solution, in step S5, the annealing heat treatment temperature is 800° C., and the annealing heat treatment time is 2 hours.
[0036] The present invention also provides a titanium alloy prepared by the above method, wherein the density of the titanium alloy is ≥99.9%.
[0037] The preparation method of the present invention can effectively expand the use range of TC4 powder particle size, and provide selective laser melting process parameters that match the use range of particle size, thereby improving the efficiency of TC4 printing. The target sample prepared by this method can achieve the same mechanical properties as the target sample prepared by using commercial TC4 titanium alloy powder in the 15-53um particle size range, greatly improving the utilization rate and production efficiency of TC4 titanium alloy powder, and increasing the TC4 titanium alloy utilization yield to more than 90%, which is much higher than the market average of 40%, and significantly reducing costs.
[0038] The preparation method of the present invention combines large powder particle size with a large layer thickness printing process, achieving comprehensive cost reduction and efficiency improvement: in terms of raw materials, the use of powder particle size range of 15-100μm can reduce costs by more than 30% compared with the 15-53μm particle size range commonly used in the market. In terms of process, the use of layer thickness of 100-180μm can increase manufacturing efficiency by 2-7 times, while ensuring that the powder within the particle size range is fully utilized. In addition, the preparation method of the present invention adopts a scanning strategy of 67° interlayer rotation, which is different from the existing method of 90° interlayer rotation scanning strategy, and uses a more optimized combination of process parameters to obtain high-density and high-performance SLM-formed TC4 alloy. In terms of forming quality, the products produced by the present invention can stably achieve a density of more than 99.9%, and a layer thickness of 100μm can achieve a stable density of more than 99.95%. In terms of performance, the samples formed using the 100-180μm layer thickness process have high strength and good plasticity after heat treatment (especially annealing at 800℃ for 2h).
[0039] The following provides specific embodiments in combination with the above technical solutions to further expand the technology of the present invention: Example 1: This embodiment provides a low-cost method for selective laser melting and printing titanium alloys: In Example 1, a low-cost selective laser melting-printed titanium alloy was prepared according to the following steps: Step S1: Providing TC4 titanium alloy powder, wherein the particle size of the powder is in the range of 15-100 μm; Step S2: drying the TC4 titanium alloy powder in a vacuum oven to obtain a printing material; Step S3: Pour the dried TC4 titanium alloy powder into the selective laser melting equipment and set the following process parameters: Laser power: 300W; Laser scanning speed: 1250mm / s; Print layer thickness: 140μm; Laser track spacing: 0.1mm; Scanning strategy: The scanning method rotates 67 degrees between layers, and a checkerboard or partition scanning strategy is used between each layer; Step S4: During the printing process, the powder spreading speed is set to 39 mm / s to complete the printing of the target sample; Step S5: After printing is completed, annealing is performed. The annealing conditions are set as follows: heating to 800°C, annealing time is 2 hours, and annealing is performed in an argon atmosphere.
[0040] Example 2: This embodiment provides a low-cost method for selective laser melting and printing titanium alloys: In Example 2, a low-cost selective laser melting-printed titanium alloy was prepared according to the following steps: Step S1: providing TC4 titanium alloy powder, wherein the particle size of the powder is in the range of 20-90 μm; Step S2: drying the TC4 titanium alloy powder in a vacuum oven to obtain a printing material; Step S3: Pour the dried TC4 titanium alloy powder into the selective laser melting equipment and set the following process parameters: Laser power: 100W; Laser scanning speed: 700mm / s; Print layer thickness: 100μm; Laser track spacing: 0.08mm; Scanning strategy: 67° rotation between layers, and a checkerboard or partitioned scanning strategy between layers. Step S4: During the printing process, the powder spreading speed is set to 8 mm / s to complete the printing of the target sample; Step S5: After printing is complete, perform an annealing heat treatment. The annealing heat treatment conditions are set as follows: heating to 750°C for 1.5 hours. During the annealing process, the substrate is protected in an argon atmosphere.
[0041] Example 3: This embodiment provides a low-cost method for selective laser melting and printing titanium alloys: In Example 3, a low-cost selective laser melting-printed titanium alloy was prepared according to the following steps: Step S1: providing TC4 titanium alloy powder, wherein the particle size of the powder is in the range of 15-100 μm.
[0042] Step S2: drying the TC4 titanium alloy powder in a vacuum oven to obtain a printing material; Step S3: Pour the dried TC4 titanium alloy powder into the selective laser melting equipment and set the following process parameters: Laser power: 500W; Laser scanning speed: 1600mm / s; Print layer thickness: 180μm; Laser track spacing: 0.15mm; Scanning strategy: The scanning method rotates 67 degrees between layers, and a checkerboard or partition scanning strategy is used between each layer; Step S4: During the printing process, the powder spreading speed is set to 50 mm / s to complete the printing of the target sample.
[0043] Step S5: After printing is complete, perform an annealing heat treatment. The annealing heat treatment conditions are set as follows: heating to 850°C for 2.5 hours. During the annealing process, the substrate is protected in an argon atmosphere.
[0044] Example 4-Example 7: The remaining conditions of Examples 4 to 7 are the same as those of Example 1, except that the laser power, laser scanning speed, and powder spreading thickness are different, and Examples 4 to 7 are tested twice, respectively named as Example 4a, Example 4b, Example 5a, Example 5b, Example 6a, Example 6b, Example 7a, and Example 7b. The preparation conditions of Examples 4 to 7 and the properties of the titanium alloys obtained by Examples 4 to 7 are shown in Table 1 below: Table 1 Mechanical properties of TC4 formed by SLM with large layer thickness Through the above embodiments and related data analysis, it is further proved that the titanium alloy materials obtained within the scope of the preparation method of the present invention can achieve significant technical effects. The present invention not only effectively improves the utilization rate of powder by optimizing process parameters (including laser power, laser scanning speed, printing layer thickness, powder spreading speed and annealing treatment conditions), but also ensures that the density, mechanical properties and high-temperature properties of the titanium alloy are equivalent to those of conventional layer thickness. Under different process conditions, the formed parts show excellent tensile strength, yield strength and elongation. The low-cost selective laser melting printing method of titanium alloy provided by the present invention can effectively optimize the key parameters in the traditional SLM process, thereby achieving a significant reduction in production costs while ensuring material quality and performance. In particular, by broadening the powder particle size range and combining appropriate printing layer thickness and annealing process, the titanium alloy obtained by the present invention not only meets high performance requirements, but also has higher production efficiency and lower material waste.
[0045] In summary, the present invention provides an efficient and low-cost titanium alloy manufacturing process, which can meet the demand for high-performance titanium alloy parts in the fields of aerospace, automobile, medical, etc. and has broad application prospects.
[0046] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "in the present embodiment", "specific example", or "some examples" means that the specific features, mechanisms, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, mechanisms, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.
[0047] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.
Claims
1. A low-cost selective laser melting printing method for titanium alloy, characterized in that: The following steps are involved: S1 provides TC4 titanium alloy powder, the TC4 titanium alloy powder having a particle size range of 15-100μm; S2. The TC4 titanium alloy powder was placed in a vacuum oven and dried to obtain printing material; S3. Pour the printing material into the selective laser melting device and set the process parameters, including: The laser power is 100-500W, the laser scanning speed is 700-1600mm / s, the printing layer thickness is 100-180μm, the laser track spacing is 0.05-0.15mm, and the scanning strategy is chessboard or partition; S4. Set the powder spreading speed during printing to complete printing of the target sample. S5. After printing is completed, the target sample is subjected to an annealing heat treatment at a temperature of 750-850° C. for 1.5-2.5 hours.
2. The low-cost selective laser melting and printing method for titanium alloy according to claim 1, characterized in that: In the step S1, the particle size of the TC4 titanium alloy powder is in the range of 20-90 μm.
3. The low-cost selective laser melting printing method for titanium alloy according to claim 1, characterized in that: In step S3, the process parameters include: laser power of 200W to 400W, laser scanning speed of 800mm / s to 1500mm / s, printing layer thickness of 100μm to 180μm, laser track spacing of 0.08mm to 0.12mm, and scanning strategy of chessboard or partition.
4. The low-cost selective laser melting and printing method for titanium alloy according to claim 3, characterized in that: In step S3, the scanning strategy is a scanning method of rotating 67 degrees between layers, and a chessboard or partition scanning strategy is adopted between each layer.
5. The low-cost selective laser melting and printing method for titanium alloy according to claim 1, characterized in that: In step S4, the powder spreading speed is 8-50 mm / s.
6. The low-cost selective laser melting and printing method for titanium alloy according to claim 1, characterized in that: In step S5, the annealing treatment condition is to raise the temperature to the annealing heat treatment temperature within 110-130 minutes, and then anneal.
7. The low-cost selective laser melting and printing method for titanium alloy according to claim 6, characterized in that: In step S5, the annealing heat treatment temperature is 800° C., and the annealing heat treatment time is 2 hours.
8. A titanium alloy prepared by the method according to any one of claims 1 to 7, characterized in that: The density of the titanium alloy is ≥99.9%.
Citation Information
Patent Citations
Method for improving utilization rate of TC4 titanium alloy powder
CN114131043A
Method for printing titanium alloy through selective laser melting
CN116875835A
Additive manufacturing process for improving efficiency of titanium alloy selective laser melting technology
CN117428208A
Cited By
3D printing method for titanium alloy four-arm spiral satellite antenna with large height-diameter ratio
CN120816000A
SLM preparation process method of TC4 powder with wide particle size distribution
CN121514532A
